DEEPFAKE TECHNOLOGY AND LEGAL - BALA, SHASHI; SHARMA, KARAN; SINGH , SANSKRITI (Trinity Law Review, 2025)
The advent of deepfake technology has ushered in a new era of digital manipulation, presenting both opportunities and challenges in various sectors. This article explores the legal intricacies surrounding deepfake technology within the framework of Indian law. It delves into the potential impact of deepfakes on privacy, defamation, intellectual property, and criminal liability, while also discussing the existing legal framework and potential legislative reforms needed to address emerging challenges.